Identification of Resistance of Local Rice Genotypes from Solok Selatan, West Sumatra to Leaf Blast (Magnaporthe oryzae) and Iron (Fe)Toxicity - Vera Septaria; Musliar Kasim; Irfan Suliansyah; Auzar Syarif; Juniarti Juniarti (Journal of Applied Agricultural Science and Technology, 2025)
Rice production in acidic soils is often limited by leaf blast disease and iron (Fe) toxicity. This study aimed to identify local rice genotypes cultivated in Solok Selatan that are tolerant to leaf blast disease and iron stresses at the vegetative stage. Ten rice genotypes, consisting of six local genotypes and four comparison genotypes, were tested under three levels of soil Fe content (11,393.12 ppm, 16,781.83 ppm, and 18,699.25 ppm) using a Completely Randomized Design with three replications. The observed variables were number of tillers, root length, leaf blast score, and Fe toxicity score. The results showed that Batang Piaman had the highest number of tillers (72.00), while Guliang Tandai Merah and Batu Hampar Putih had the longest roots (50.67 cm and 49.78 cm). Guliang Tandai Merah had the lowest leaf blast score (2.89), and together with Batang Piaman, also showed low Fe toxicity scores (3.56 and 3.22), indicating good tolerance. In contrast, Simauang and IR64 were the most susceptible against iron toxicity compared to other rice genotypes. Principal Component Analysis (PCA) explained 81.80% of the total variation and placed Batang Piaman and Cilamaya Muncul in the quadrant of high tolerance and good agronomic traits. Cluster analysis grouped the genotypes into three major clusters, with Guliang Tandai Merah and Batu Hampar Putih forming a distinct group based on strong root traits. Although no genotype was completely resistant, Batang Piaman and Guliang Tandai Merah are promising candidates for breeding programs targeting leaf blast and Fe toxicity tolerance.